Dewatering method og hard-to-dewatering sludge
Patent Information
- Application Number
- JP2023137040
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-25
- Publication Date
- 2025-03-07
AI Technical Summary
【0006】 本発明における汚泥脱水剤を使用することで、従来の汚泥脱水剤では処理が困難な難脱水性汚泥に対して汚泥脱水性の向上を達成することができる。
Smart Images

Figure 2025031066000001 
Figure 2025031066000002 
Figure 2025031066000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a sludge dewatering method that uses a water-soluble polymer as a sludge dewatering agent, and more particularly, to a sludge dewatering method that improves the dewaterability of difficult-to-dewater sludge by using a water-soluble polymer having a specific composition. [Background technology]
[0002] Water-soluble polymers are used as sludge dehydration agents in the dehydration of organic sludge, such as primary raw sludge settled from sewage, excess sludge or mixed raw sludge settled from effluent from an activated sludge tank, and digested sludge obtained by subjecting these sludges to anaerobic digestion. Generally, polyacrylamide (PAM) water-soluble polymers are widely used as water-soluble polymers. However, in recent years, PAM sludge dewatering agents alone are often ineffective for hard-to-dewater sludge, and in such cases, water-soluble polymers with high cation density and amidine structural units (amidine water-soluble polymers) are used to address the issue. However, amidine-based water-soluble polymers are relatively expensive and require a high addition rate to exert their flocculation effect, so various sludge dewatering methods have been proposed that combine amidine-based water-soluble polymers with other polymers. For example, Patent Document 1 discloses a sludge dewatering agent that combines an amidine polymer with a cationic polymer such as a PAM polymer. However, it is necessary to select a polymer to be combined with the amidine polymer depending on the target sludge properties, and in recent years, it is often difficult to treat difficult-to-dewater sludge even with these methods. Therefore, polymers that are more effective than amidine polymers have been proposed. For example, Patent Documents 2 and 3 disclose the use of water-in-oil emulsions of aqueous polymers with specific compositions and physical properties as sludge dewatering agents. These are highly cross-linked or branched polymers, and the technical idea is that when added to the target sludge, they are effective when used in a mixed state of water-soluble and water-swellable or completely water-swellable. However, it is difficult to obtain the desired effect from these conventional polymers, particularly for difficult-to-dewater sludge that has extremely high M alkalinity and electrical conductivity, and there is a demand for the application of more effective polymers for difficult-to-dewater sludge.
[0003] [Patent Document 1] Japanese Patent Application Publication No. 6-218400 [Patent Document 2] JP 2012-170943 A [Patent Document 3] JP 2012-228664 A Summary of the Invention [Problem to be solved by the invention]
[0004] The present invention relates to a method for dehydrating sludge using a sludge dehydrating agent, and an object of the present invention is to provide a sludge dehydration method that improves the dehydration ability of difficult-to-dewater sludge having extremely high M alkalinity and electrical conductivity. [Means for solving the problem]
[0005] As a result of intensive research conducted to solve the above problems, the present inventors discovered that it is possible to improve sludge dewaterability by using a sludge dewatering agent containing a water-soluble polymer having a specific composition for difficult-to-dewater sludge having an M alkalinity of 3000 mg / L or more and an electrical conductivity of 500 mS / m or more, which led to the present invention. Effect of the Invention
[0006] By using the sludge dewatering agent of the present invention, it is possible to achieve improvement in the dewaterability of sludge that is difficult to dewater using conventional sludge dewatering agents. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0007] The water-soluble polymer in the present invention has as its constituent units 30 to 90 mol % of a cationic monomer represented by the following general formula (1) and 10 to 70 mol % of a nonionic monomer. The cationic monomer represented by the general formula (1) is preferably 40 to 90 mol %, more preferably 60 to 90 mol %, and even more preferably 75 to 90 mol %. This is because a medium to high molar ratio of the cationic monomer tends to be able to treat a wide range of sludge properties. TIFF2025031066000001.tif3181 General formula (1) R1 is hydrogen or a methyl group, R2 and R3 are alkyl groups or alkoxy groups having 1 to 3 carbon atoms, and may be the same or different, A is oxygen or NH, B is an alkylene group or alkoxylene group having 2 to 4 carbon atoms, and X1 is an anion.
[0008] The cationic monomer represented by the general formula (1) is a halogenated aryl compound such as dimethylaminoethyl (meth)acrylate or dimethylaminopropylacrylamide, such as benzyl chloride, or a quaternary product of an alkyl halide having 7 to 20 carbon atoms. For example, it is (meth)acryloyloxyethyl dimethylbenzyl ammonium chloride, (meth)acryloylaminopropyl dimethylbenzyl ammonium chloride, etc. Two or more of these may be combined.
[0009] The nonionic monomers used in the present invention include (meth)acrylamide, N,N'-dimethylacrylamide, acrylonitrile, (meth)acrylate-2-hydroxyethyl, diacetone acrylamide, N-vinylpyrrolidone, N-vinylformamide, N-vinylacetamide, acryloylmorpholine, etc. Among these, (meth)acrylamide is preferred. Two or more of these may be used in combination.
[0010] In addition to the cationic monomer and nonionic monomer represented by the general formula (1), an anionic monomer may be used to the extent that it does not impair the effect of the water-soluble polymer in the present invention. Examples of the anionic monomer include (meth)acrylic acid or its alkali metal salts or ammonium salts such as sodium salt, maleic acid or its alkali metal salts, and acrylamidoalkanesulfonic acids such as acrylamido-2-methylpropanesulfonic acid or its alkali metal salts or ammonium salts. When an anionic monomer is used, it is preferably used in an amount of 10 mol % or less.
[0011] A crosslinkable monomer is used when producing the water-soluble polymer of the present invention. Although it depends on the type of crosslinkable monomer, it is present in the range of 10 ppm or more and less than 40 ppm relative to the total amount of monomers. It is preferably 15 ppm or more and less than 40 ppm, more preferably 20 ppm or more and less than 40 ppm. If it is less than 10 ppm, the coagulation treatment performance is not exhibited. If it is 40 ppm or more, depending on the structure and composition ratio of the polymer, it is a stage where it transitions to water swelling, and it becomes difficult to exhibit the effect of the water-soluble polymer of the present invention. The present invention has found that a water-soluble polymer obtained by using and polymerizing a cationic monomer represented by general formula (1) and a crosslinkable monomer in a certain range is effective for a specific difficult-to-dewater sludge. Examples of crosslinkable monomers include N,N'-methylenebis(meth)acrylamide, triallylamine, ethylene glycol dimethacrylate, diethylene glycol dimethacrylate, triethylene glycol dimethacrylate, tetraethylene glycol dimethacrylate, 1,3-butylene glycol dimethacrylate, polyethylene glycol di(meth)acrylate, N-vinyl(meth)acrylamide, N-methylallylacrylamide, glycidyl acrylate, polyethylene glycol diglycidyl ether, acrolein, glyoxal, vinyltrimethoxysilane, and the like, with N,N'-methylenebis(meth)acrylamide being preferred.
[0012] The water-soluble polymer in the present invention can be produced by copolymerizing a monomer mixture containing a cationic monomer represented by the general formula (1), a nonionic monomer, and a crosslinkable monomer. The polymerization is carried out by preparing an aqueous solution of these monomers and then carrying out a known copolymerization method. For example, after polymerization by aqueous solution polymerization, water-in-oil emulsion polymerization, water-in-oil dispersion polymerization, dispersion polymerization in salt water, etc., the product can be in any form, such as an aqueous solution, a dispersion in salt water, a water-in-oil emulsion, or a powder. Among these, water-in-oil emulsions are preferred because they are easy to adjust the molecular weight.
[0013] In the case of a water-in-oil emulsion, it can be appropriately produced according to the methods described in JP-A-10-137797, JP-A-10-140496, JP-A-2011-194347, etc. That is, a monomer mixture containing a cationic monomer, a nonionic monomer, and a crosslinkable monomer is mixed with water, an oily substance consisting of at least a water-immiscible hydrocarbon, and at least one surfactant having an effective amount and HLB for forming a water-in-oil emulsion, and the mixture is stirred vigorously to form a water-in-oil emulsion, followed by polymerization.
[0014] Examples of oily substances made of hydrocarbons used as dispersion media include paraffins, naphthenes, mineral oils such as kerosene, light oil, and medium-weight oil, synthetic hydrocarbon oils having substantially the same ranges of boiling point, viscosity, and other properties as these, and mixtures thereof. The content is in the range of 20% by mass to 50% by mass, and preferably 20% by mass to 35% by mass, based on the total amount of the water-in-oil emulsion.
[0015] An example of at least one surfactant having an effective amount and HLB for forming a water-in-oil emulsion is a nonionic surfactant with an HLB of 1 to 15, and specific examples thereof include sorbitan monooleate, sorbitan monostearate, sorbitan monopalmitate, polyoxyethylene nonylphenyl ether, etc. The amount of these surfactants to be added is 0.5 to 10% by mass, preferably 1 to 5% by mass, based on the total amount of the water-in-oil emulsion.
[0016] The polymerization concentration of the monomer is in the range of 20 to 60% by mass, and the polymerization concentration and temperature are appropriately set depending on the monomer composition and the selection of the initiator. The polymerization temperature is 20 to 80°C, preferably 20 to 60°C. A radical polymerization initiator is used to start the polymerization. These initiators can be either oil-soluble or water-soluble. Examples of oil-soluble azo initiators include 2,2'-azobisisobutyronitrile, dimethyl-2,2'-azobisisobutyrate, 1,1'-azobis(cyclohexane-1-carbonitrile), 2,2'-azobis(2-methylbutyronitrile), dimethyl-2,2'-azobis(2-methylpropionate), and 2,2'-azobis(4-methoxy-2,4-dimethylvaleronitrile).
[0017] Examples of water-soluble azo initiators include 2,2'-azobis(amidinopropane) dihydrochloride, 2,2'-azobis[2-(5-methyl-imidazolin-2-yl)propane] dihydrochloride, 4,4'-azobis(4-cyanovaleric acid), etc. Examples of peroxide initiators include ammonium or potassium peroxodisulfate, hydrogen peroxide, benzoyl peroxide, lauroyl peroxide, octanoyl peroxide, succinic peroxide, t-butylperoxy-2-ethylhexanoate, t-butyl hydroperoxide, etc. Redox initiators in which these peroxide initiators are combined with sodium sulfite, sodium hydrogen sulfite, trimethylamine, tetramethylethylenediamine, etc. can also be used.
[0018] In order to adjust the degree of polymerization, it is effective to use isopropyl alcohol in an amount of 0.1 to 5% by mass based on the monomer, or sodium formate in an amount of 0.01 to 0.5% by mass based on the monomer.
[0019] After polymerization, a hydrophilic surfactant called a phase inversion agent is added as necessary to make the emulsion particles covered with an oil film more compatible with water and to make the water-soluble polymer inside more soluble, and then the emulsion is diluted with water and used for various purposes. Examples of hydrophilic surfactants include cationic surfactants and nonionic surfactants with HLB of 9 to 15, such as polyoxyethylene polyoxypropylene alkyl ethers and polyoxyethylene alcohol ethers.
[0020] The sludge dehydration agent of the present invention is applied to sludge that is difficult to dewater. In particular, digested sludge generated from the process of anaerobic treatment of organic substances such as food manufacturing residues, sludge, and biomass is often difficult to dewater because it has a low fiber content and a high anion content. Further indicators of difficulty in dewatering include M alkalinity and electrical conductivity. When these are high, the treatment effect of conventional PAM-based polymers and amidine-based polymers decreases. In particular, when the M alkalinity is 3000 mg / L or more and the electrical conductivity is 500 mS / m or more, the treatment effect decreases drastically. Among digested sludges, biomass digested sludge obtained by supplying biomass, a resource containing organic matter derived from living organisms, to a digester and subjecting it to anaerobic treatment has extremely high values of M alkalinity and electrical conductivity. Examples of organic matter derived from living organisms include organic wastewater, organic waste, or manure from the food industry, paper industry, livestock industry, etc., organic waste such as sludge from urban sewage, resource crops such as corn and sugar cane, and waste generated in the treatment process of these crops. In order to treat these sludges with high M alkalinity and electrical conductivity using conventional sludge dehydration agents, the addition rate must be significantly increased to about 1000 to 2000 ppm relative to the sludge liquid volume, or even if the addition rate is increased beyond that, the effect is often poor. On the other hand, the water-soluble polymer of the present invention is also effective in sludge with an M alkalinity of 3000 mg / L or more and an electrical conductivity of 500 mS / m or more. The higher these values, the more pronounced the difference in effectiveness becomes compared to conventional sludge dehydration agents, so it is preferable to apply it to sludge with an M alkalinity of 3000 mg / L or more and an electrical conductivity of 1000 mS / m or more, and more preferably to sludge with an M alkalinity of 5000 mg / L or more and an electrical conductivity of 1000 mS / m or more.
[0021] In the present invention, M alkalinity is a value measured by the amount of hydrochloric acid consumed by alkaline components such as carbonates, hydrogen carbonates, or hydroxides contained in sludge, and is expressed by converting the amount of hydrochloric acid required to neutralize the sludge to pH 4.8 into the equivalent calcium carbonate (CaCO3) concentration (mg / L), and conforms to the value generally used as an index of sludge putrefaction and fermentation. For example, the measurement method is to collect 50 mL of sludge in a 200 mL beaker, drop 1 / 10 N hydrochloric acid while stirring with a stirrer until the pH reaches 4.8, measure the amount of drop (g), and calculate the value according to the following formula. M alkalinity (mg / L) = amount of 1 / 10N hydrochloric acid dropped x titer of 1 / 10N hydrochloric acid x 100
[0022] The water-soluble polymer in the present invention needs to have a certain molecular weight in order to perform as a sludge dewatering agent. Intrinsic viscosity is an index of molecular weight. When intrinsic viscosity is used as an index, the intrinsic viscosity of the water-soluble polymer in a 0.1 N saline solution measured at 25°C is in the range of 3 to 10 dL / g. If it is lower than 3 dL / g, the effect is difficult to be exhibited, and if it is higher than 10 dL / g, dispersibility becomes poor and the effect is reduced. An intrinsic viscosity in the range of 4 to 7 dL / g is particularly preferable. The intrinsic viscosity is a value measured using an automatic viscosity measuring device, SS-120-L1 type, manufactured by Shibayama Scientific Machinery Works, Ltd. Any device of the same type can be used as appropriate. In the present invention, the water-soluble polymer is precipitated in a 1N saline or sodium nitrate solvent that is generally used in intrinsic viscosity measurement due to the presence of the cationic monomer represented by the general formula (1), and therefore cannot be measured. Therefore, in the present invention, the intrinsic viscosity is measured in a 0.1N saline solution. The weight average molecular weight is preferably in the range of 1 million to 5 million, and more preferably in the range of 1 million to 3 million.
[0023] Furthermore, the viscosity of a 0.5% by mass salt solution of the water-soluble polymer in the present invention can also be used as an index of molecular weight. That is, the viscosity of a 2% by mass ammonium sulfate solution at 0.5% by mass of the water-soluble polymer measured at 25°C is preferably 5 mPa·s or more and 100 mPa·s or less, more preferably 10 mPa·s or more and 100 mPa·s or less, and even more preferably 10 mPa·s or more and 70 mPa·s or less. This viscosity of a 0.5% by mass salt solution is a value measured using a Brookfield viscometer with a No. 1 rotor at 60 rpm. As the Brookfield viscometer, a TVB-10M manufactured by Toki Sangyo or the like can be used.
[0024] The particle size of the polymer in the present invention is preferably 500 nm or less as measured by dynamic light scattering. Dynamic light scattering measurement is performed using an ELS-Z (zeta potential / particle size measurement system) manufactured by Otsuka Electronics as follows. A diluted emulsion with a polymer concentration of 0.01% by mass is prepared and placed in a plastic deposit cell (material: methacrylate) with an optical path length of 10 mm. Measurement conditions are a temperature of 25°C, solvent: mineral spirits containing 4% by mass of sorbitan fatty acid ester (HLB=4.0-5.0), and a refractive index of 1.438, and the particle size is determined by analysis using the cumulant method. Note that similar particle size measurement devices using the same measurement principle can be used as appropriate.
[0025] The difficult-to-dewater sludge to which the sludge dehydrating agent of the present invention is applied is sludge with a high organic content ratio that is more difficult to dehydrate. Specifically, the organic matter content of the sludge (VSS, loss on ignition in suspended solids, mass % vs. SS; suspended suspended solids), which is an index of organic matter, is 45 mass % or more. In recent years, there has been a tendency for VSS and VTS (loss on ignition in evaporation residue, mass % vs. TS) to increase in these organic sludges, and since the effect of the sludge dehydrating agent of the present invention is more remarkable compared to conventional sludge dehydrating agents, sludge with a VSS of 60 mass % or more is preferable, and 70 mass % or more is even more preferable. Note that the various measured values are measured based on a standard method (sewage test method).
[0026] The sludge dewatering agent may contain a water-soluble polymer other than the water-soluble polymer of the present invention. In order to be effective with the sludge targeted by the present invention, the sludge dewatering agent preferably contains the water-soluble polymer of the present invention in an amount of 50% by mass or more based on the total mass of the sludge dewatering agent.
[0027] The sludge type applicable as the sludge dehydration agent of the present invention is a difficult-to-dehydrate sludge with an M alkalinity of 3000 mg / L or more and an electric conductivity of 500 mS / m or more, and is particularly effective for digested sludge, and is particularly effective for biomass digested sludge. The agent is diluted with water to an arbitrary concentration and added to these sludges. The range of 0.01 to 1.0 mass% is preferable. The addition rate to the sludge varies depending on the sludge type and dehydration model, but is 100 to 10,000 ppm relative to the amount of sludge liquid, but is preferably 1000 ppm or more, more preferably 1400 ppm or more, even more preferably 1600 ppm or more, and even more preferably 2000 ppm or more. This is because a higher addition rate of the polymer tends to be required to cause a flocculation action on the target sludge compared to general sludge. In the case of conventional polymers, even if 2000 ppm or more is added, improvement in the flocculation effect is not observed in many cases, but with the water-soluble polymer of the present invention, improvement in the flocculation effect can be obtained even at such a high addition rate. Furthermore, it may be used in combination with inorganic flocculants such as aluminum sulfate, aluminum chloride, polyaluminum chloride, polyferrous sulfate, polyferric sulfate, and ferric chloride.
[0028] After the sludge dehydrating agent addition treatment in the present invention, a dehydrator such as a screw thickener, centrifugal thickener, elliptical disk thickener, belt press, centrifugal dehydrator, screw press, multiple disk dehydrator, rotary press, filter press, etc. can be arbitrarily applied. EXAMPLES
[0029] The sludge dewatering method of the present invention will be specifically described below, but the present invention is not limited to the following examples.
[0030] (Production of Water-Soluble Polymer Samples A to E) In a four-necked 500 mL separable flask equipped with a stirrer, a thermometer, and a nitrogen inlet tube, 5.0 g of sorbitan monooleate and 2.5 g of polyoxyethylene sorbitan monooleate were charged and dissolved in 145.0 g of naphthenic oil with a boiling point of 190 ° C to 230 ° C. Separately, 240.0 g of 80 mass % acryloyloxyethyl dimethylbenzyl ammonium chloride (hereinafter abbreviated as DMBZ), 25.3 g of 50 mass % acrylamide (abbreviated as AAM), 0.2 g of sodium formate, 0.0058 g of methylene bisacrylamide, and pure water were collected and added. The oil and the aqueous solution were mixed and emulsified with a homogenizer. The monomer composition at this time was DMBZ / AAM = 80 / 20 (mol %). The temperature of the obtained emulsion monomer solution was kept at 24-26°C, and nitrogen substitution was performed for 30 minutes. Then, 0.05 g (0.02 mass% relative to monomer) of azo-based initiator 2,2'-azobis(4-methoxy-2,4-dimethylvaleronitrile) (Fujifilm Wako Pure Chemical Industries, Ltd. V-70) was added to start the polymerization reaction. The reaction was completed by polymerization at 27°C for 3 hours and at 60°C for 1 hour. The composition and physical properties of this water-soluble polymer sample A are shown in Table 1. In addition, water-soluble polymer samples B to E were produced by changing the monomer composition and amount of crosslinkable monomer under the same polymerization conditions as sample A. The compositions and physical properties of these samples are shown in Table 1.
[0031] (Table 1) TIFF2025031066000002.tif3491 Monomer; DMBZ: acryloyloxyethyl dimethylbenzyl ammonium chloride, AAM: acrylamide Crosslinker: methylenebisacrylamide, Addition rate: ppm to total monomer amount Product form: EM: water-in-oil emulsion Viscosity of aqueous salt solution: Viscosity (mPa s) measured at 25°C when the polymer is dissolved in a 2% by mass aqueous ammonium sulfate solution to give a polymer concentration of 0.5% by mass. Intrinsic viscosity: The intrinsic viscosity of a water-soluble polymer in a 0.1 N saline solution measured at 25°C.
[0032] Water-soluble polymer samples 1 to 7, which are generally used as sludge dewatering agents, were prepared or prepared. Their compositions and physical properties are shown in Table 2.
[0033] (Table 2) TIFF2025031066000003.tif4291 Monomer; DMQ: acryloyloxyethyltrimethylammonium chloride; DMC: methacryloyloxyethyltrimethylammonium chloride; AAM: acrylamide, AAC: acrylic acid Product form: P: powder, EM: water-in-oil emulsion Saline solution viscosity: Viscosity (mPa s) measured at 25°C when the polymer is dissolved in 4 mass% saline solution to a concentration of 0.5 mass%.
[0034] Example 1 A dewatering test was conducted on biomass digested sludge (pH 7.8, electrical conductivity 2700 mS / m, SS content 19750 mg / L, VSS 69.6 mass% / SS, VTS 59.7 mass% / TS, M-alkalinity 10633 mg / L, anion content 12.7 meq / L). 100 mL of sludge was collected in a plastic beaker, and a 0.4% by mass aqueous solution of water-soluble polymer sample A in Table 1 was added to the sludge at 1600 ppm (polymer purity), and the mixture was stirred at 1000 rpm for 30 seconds in a CST measuring device, filtered through a 40 mesh, and the amount of filtrate was measured after 60 seconds. The sludge was then pressed using a nylon filter cloth (#202) at a pressure of 3 kg / cm. 2 The cake was dehydrated at 105°C for 30 seconds and the moisture content was measured (dried at 105°C for 20 hours). Similar tests were also carried out by changing the addition rate of the water-soluble polymer sample and the sample. The results are shown in Table 3.
[0035] (Comparative Example 1) Using the same sludge as in Example 1, a similar test was carried out using the water-soluble polymer samples in Table 2. The results are shown in Table 3.
[0036] (Table 3) TIFF2025031066000004.tif4769
[0037] Example 2 A dewatering test was conducted on biomass digested sludge (pH 7.6, electrical conductivity 2440 mS / m, SS content 26250 mg / L, VSS 74.3 mass% / SS, VTS 69.6 mass% / TS, M-alkalinity 10431 mg / L, anion content 13.1 meq / L). 100 mL of sludge was collected in a plastic beaker, and a 0.2% by mass aqueous solution of water-soluble polymer sample A in Table 1 was added at 1400 ppm or 1800 ppm (polymer purity) to the sludge liquid volume. The mixture was transferred to another beaker 20 times and stirred with a spatula 100 times, then filtered through a 40 mesh filter, and the amount of filtrate was measured after 60 seconds. The sludge was then pressed using a nylon filter cloth (#202) at a pressure of 3 kg / cm. 2 The cake was dehydrated at 105°C for 60 seconds and the moisture content of the cake was measured (dried at 105°C for 20 hours). The results are shown in Table 4.
[0038] (Comparative Example 2) Using the same sludge as in Example 2, a similar test was carried out using the water-soluble polymer sample in Table 2. The results are shown in Table 4.
[0039] (Table 4) TIFF2025031066000005.tif3169
[0040] Example 3 A dewatering test was conducted on biomass digested sludge (pH 7.8, electrical conductivity 1274 mS / m, SS content 7000 mg / L, VSS 71.4 mass% / SS, VTS 68.8 mass% / TS, M-alkalinity 6569 mg / L, anion content 5.2 meq / L). 100 mL of sludge was collected in a plastic beaker, and a 0.3% by mass aqueous solution of water-soluble polymer sample A in Table 1 was added to the sludge at 1650 ppm or 1950 ppm (polymer purity) relative to the sludge liquid volume. After stirring at 1000 rpm for 30 seconds in a CST measuring device, the mixture was filtered through a 40 mesh and the amount of filtrate was measured after 60 seconds. The sludge was then pressed using a nylon filter cloth (#202) at a pressure of 3 kg / cm. 2 The cake was dehydrated at 105° C. for 30 seconds and the moisture content of the cake was measured (dried at 105° C. for 20 hours). The results are shown in Table 5.
[0041] (Comparative Example 3) Using the same sludge as in Example 3, a similar test was carried out using the water-soluble polymer sample in Table 2. The results are shown in Table 5.
[0042] (Table 5) TIFF2025031066000006.tif3169
[0043] Example 4 A dewatering test was conducted on biomass digested sludge (pH 8.0, electrical conductivity 2830 mS / m, SS content 18000 mg / L, VSS 76.4 mass% / SS, VTS 64.3 mass% / TS, M-alkalinity 15795 mg / L, anion content 15.1 meq / L). 100 mL of sludge was collected in a plastic beaker, and a 0.4% by mass aqueous solution of water-soluble polymer sample A in Table 1 was added to the sludge at 2600 ppm (polymer purity) relative to the sludge volume. After stirring at 1000 rpm for 30 seconds in a CST measuring device, the sludge was filtered through a 40 mesh and the filtrate volume was measured. The sludge was then pressed using a nylon filter cloth (#202) at a pressure of 3 kg / cm. 2 The cake was dehydrated at 105°C for 30 seconds and the moisture content was measured (dried at 105°C for 20 hours). Similar tests were also carried out using different water-soluble polymer samples. The results are shown in Table 6.
[0044] (Comparative Example 4) Using the same sludge as in Example 4, a similar test was carried out using the water-soluble polymer sample in Table 2. The results are shown in Table 6.
[0045] (Table 6) TIFF2025031066000007.tif2969
[0046] Example 5 A dewatering test was conducted on biomass digested sludge (pH 8.4, electrical conductivity 3040 mS / m, SS content 15000 mg / L, VSS 66.7 mass% / SS, VTS 58.9 mass% / TS, M-alkalinity 18114 mg / L, anion content 19.8 meq / L). 100 mL of sludge was collected in a plastic beaker, and a 0.4% by mass aqueous solution of water-soluble polymer sample A in Table 1 was added to the sludge at 3600 ppm (polymer purity), and the mixture was stirred at 1000 rpm for 30 seconds in a CST measuring device, filtered through a 40 mesh, and the amount of filtrate was measured after 60 seconds. The sludge was then pressed using a nylon filter cloth (#202) at a pressure of 3 kg / cm. 2 The cake was dehydrated at 105°C for 30 seconds and the moisture content was measured (dried at 105°C for 20 hours). Similar tests were also carried out using different water-soluble polymer samples. The results are shown in Table 7.
[0047] (Comparative Example 5) Using the same sludge as in Example 5, a similar test was carried out using the water-soluble polymer sample in Table 2. The results are shown in Table 7.
[0048] (Table 7) TIFF2025031066000008.tif2969
[0049] For the difficult-to-dewater sludge targeted by the present invention, conventional polyacrylamide-based polymers and amidine-based polymers were ineffective in dewatering sludge even at high addition rates, whereas the application of a sludge dewatering agent containing the water-soluble polymer of the present invention showed excellent dewatering effects. It was confirmed that it is possible to treat difficult-to-dewater sludge with high alkalinity and high electrical conductivity, which was ineffective or could not be treated with conventional sludge dewatering agents.
Claims
1. A method for dewatering sludge, comprising adding a sludge dewatering agent containing a water-soluble polymer obtained by polymerizing a monomer mixture containing 30 to 90 mol % of a cationic monomer represented by the following general formula (1) and 10 to 70 mol % of a nonionic monomer, and a monomer mixture containing 10 ppm or more and less than 40 ppm by mass of a crosslinkable monomer relative to the monomer mixture, to difficult-to-dewater sludge having an M alkalinity of 3,000 mg / L or more and an electrical conductivity of 500 mS / m or more: General formula (1) R 1 is hydrogen or a methyl group, R 2 , R 3 are alkyl groups or alkoxy groups having 1 to 3 carbon atoms, and may be the same or different. A is oxygen or NH, B is an alkylene group or alkoxylene group having 2 to 4 carbon atoms, X 1 represents an anion.
2. 2. The method for dewatering sludge according to claim 1, wherein the water-soluble polymer has an intrinsic viscosity in a 0.1 N saline solution measured at 25° C. of 3 to 10 dL / g.
3. 3. The method for dewatering sludge according to claim 1, wherein the water-soluble polymer is in the form of a water-in-oil emulsion.
4. 3. The method for dewatering sludge according to claim 1, wherein the particle size of the water-soluble polymer is 500 nm or less.
5. 2. The method for dewatering sludge according to claim 1, wherein the difficult-to-dewater sludge is digested sludge.